2022
DOI: 10.1242/dev.199625
|View full text |Cite
|
Sign up to set email alerts
|

Msl3 promotes germline stem cell differentiation in female Drosophila

Abstract: Gamete formation from germline stem cells (GSCs) is essential for sexual reproduction. However, the regulation of GSC differentiation are incompletely understood. Set2, which deposits H3K36me3 modifications, is required for GSC differentiation during Drosophila oogenesis. We discovered that the H3K36me3 reader Male-specific lethal 3 (MSL3) and histone acetyltransferase complex Ada2a-containing (ATAC) cooperate with Set2 to regulate GSC differentiation in female Drosophila. MSL3, acting independent from the res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 167 publications
6
47
1
Order By: Relevance
“…Our bulk RNA-seq data, as well as the available scRNA-seq data indicated that RpS19b was highly expressed in GSCs, decreased during differentiation in the cyst stages and was greatly decreased in expression in early egg chambers, consistent with previous reports ( Fig. 2 A,B) ( McCarthy et al, 2021 ; Sarkar et al, 2021 preprint). To further validate this expression pattern, we probed the expression of RpS19b in vivo using in situ hybridization as well as an RpS19b::GFP line that is under endogenous control elements ( McCarthy et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…Our bulk RNA-seq data, as well as the available scRNA-seq data indicated that RpS19b was highly expressed in GSCs, decreased during differentiation in the cyst stages and was greatly decreased in expression in early egg chambers, consistent with previous reports ( Fig. 2 A,B) ( McCarthy et al, 2021 ; Sarkar et al, 2021 preprint). To further validate this expression pattern, we probed the expression of RpS19b in vivo using in situ hybridization as well as an RpS19b::GFP line that is under endogenous control elements ( McCarthy et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…Our bulk RNA-seq data, as well as the available scRNA-seq data indicated that RpS19b was highly expressed in GSCs, decreased during differentiation in the cyst stages and was greatly decreased in expression in early egg chambers, consistent with previous reports (Fig (McCarthy et al, 2021;Sarkar et al, 2021). To further validate this expression pattern, we probed the expression of RpS19b in vivo using in situ hybridization as well as an RpS19b::GFP line that is under endogenous control elements (McCarthy et al, 2021). We found that RpS19b was present in the GSCs and diminishes in the cyst stages both at the mRNA and protein level (Figure 2C-E').…”
Section: Resultssupporting
confidence: 92%
“…To determine if the bulk RNA-seq data recapitulates genuine changes in gene expression, we compared the expression of ribosomal small subunit protein 19b ( RpS19b ) in bulk RNA-seq to scRNA-seq data. Our bulk RNA-seq data, as well as the available scRNA-seq data indicated that RpS19b was highly expressed in GSCs, decreased during differentiation in the cyst stages and was greatly decreased in expression in early egg chambers, consistent with previous reports ( Fig 2A-B ) (McCarthy et al, 2021; Sarkar et al, 2021). To further validate this expression pattern, we probed the expression of RpS19b in vivo using in situ hybridization as well as an RpS19b::GFP line that is under endogenous control elements (McCarthy et al, 2021).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations